Examining RE and Emotional Distress in Population With Existing Cardiovascular Disease and/or Cardiovascular Disease Risk Factors and Those Without. (October 2017) - Daire, Andrew P.; Liu, Xun; Williams, Brooke; Tucker, Kelsee; Wheeler, Naomi; Moumouris, Teddy; Liekweg, Kimberly; Peoples, Taylar
Cardiovascular (CV) disease is the leading cause of death in the United States (Hoyert & Xu, 2012), and low-income and ethnic minorities are disproportionally affected. Relationship education (RE) interventions have been shown to improve relationship quality and reduce distress in individuals and couples, including low-income and ethnic minority populations. This study examined the effect of an evidenced-based, individual-oriented, RE intervention, within my reach, (WMR), on emotional distress in a population of mostly low-income and ethnic minority individuals with existing CV disease and/or CV disease risk factors (CVD) to those without disease or risk factors (non-CVD). Results showed significant improvements in overall distress for both the CVD and non-CVD groups, but neither group improved significantly more than the other. The authors found similar changes in distress levels when we examined a subset of the population that met the criteria for clinical distress. Also, data showed that CVD participants presented with significantly greater overall distress than non-CVD participants. These findings are consistent with prior research that showed the effectiveness of the WMR curriculum in stress reduction. Furthermore, this study contributes knowledge about a unique population, individuals with CV disease and/or CVD, who may greatly benefit from interventions focused on stress reduction.